Exploration of the functional properties of hydrothermally treated Canary seed (Phalaris canariensis L.) flour for food applications - Lovemore Nkhata Malunga; Sijo Joseph Thandapilly; Claudia Narvaez-Bravo; Nancy Ames (Food Chemistry Advances)
This research investigated the changes in physiochemical and techno-functional properties, protein nutritional quality, and microbial properties of Canary seed flour following hydrothermal treatment. Four hairless Canary seeds were dehulled, steamed, dried, and ground to flour. The hydrothermal treatment increased the mean particle size (∼80 %), damaged starch content (∼260 %), and water absorption capacity (∼46 %), while not affecting the flour’s acidity (pH ∼6.4), bulk density (∼0.6 g/mL), or oil absorption capacity (∼2.0 %). Hydrothermal treatment affected all the pasting and thermal properties of Canary seed flour except for the pasting temperature. Nutritionally, the treatment significantly improved in vitro protein digestibility, although it did not affect protein content (∼20.0 %), amino acid content, amino acid score (0.3 – 0.5), or in vitro protein digestibility corrected amino acid score (in vitro PDCAAS) (0.2 – 0.4). Most importantly, heat treatment significantly enhanced the microbial quality by eliminating the microbial load in the raw Canary seed flour, ensuring the safety of the product. Our results suggest that hydrothermally treated canary seed flour has improved physicochemical and functional properties, making it a better substitute than its raw counterpart.